Forced formalization and informal sector: A simple Chayanov model. Issue 4 (1st August 2022) - Sengupta, Atanu; De, Sanjoy
Abstract: Recently, the government of India has promulgated a sudden move of demonetisation. Such move can be considered as a type of forced formalization. Porta and Shleifer (2014) deals with the issue of formal informal interactions and comes out with an interesting conclusion. The informal sector does not merely exist for taking advantage of legal loopholes. Even if these loopholes are somehow stitched, the informal sector will not become formal. The clue perhaps lies in an old view expressed by Chayanov that in certain circumstances an informal sector can outperform a modern capitalist sector. This paper is a modest attempt to include this clue in a formal model of the simplest possible type that tries to unravel the relation between formal and informal sector as also the consequences of policies that leads to forced formalisation.